Psychophysiological Stress and Recovery in Sports Science Students: Evidence from RESTQ-Sport 76 Monitoring - Setiowati, Anies; Handayani, Oktia Woro Kasmini; Rahayu, Setya; Cahyati, Widya Hary; Sumartiningsih, Sri (Journal of Creativity Student, 2025)
Sports students face multidimensional pressures from academic demands and physical training, which have the potential to cause chronic stress and impaired recovery if not managed properly. This study aimed to analyze the stress and recovery profiles of sports students based on gender and type of sport (individual/team) using the RESTQ-Sport 76 instrument. Methodology: A cross-sectional study was conducted on 161 students of the Faculty of Sport Science, Semarang State University. Data were collected using the Indonesian version of the RESTQ-Sport 76 and statistically analyzed using t-tests to compare differences based on gender and type of sport. Results: There was no significant difference in stress and recovery levels between male and female students (p>0.05), although males tended to have higher recovery scores. Similarly, there was no significant difference between individual and team athletes. However, sleep and rest quality were identified as critical aspects that need to be improved. Conclusion: Stress and recovery in sports students are influenced by academic and training factors in general, not solely by gender or type of sport. Holistic monitoring and needs-based interventions are recommended to improve the well-being of student athletes.